2023
DOI: 10.1186/s13613-023-01181-2
|View full text |Cite
|
Sign up to set email alerts
|

SPLF/SMFU/SRLF/SFAR/SFCTCV Guidelines for the management of patients with primary spontaneous pneumothorax

Stéphane Jouneau,
Jean-Damien Ricard,
Agathe Seguin-Givelet
et al.

Abstract: Introduction Primary spontaneous pneumothorax (PSP) is the presence of air in the pleural space, occurring in the absence of trauma and known lung disease. Standardized expert guidelines on PSP are needed due to the variety of diagnostic methods, therapeutic strategies and medical and surgical disciplines involved in its management. Methods Literature review, analysis of the literature according to the GRADE (Grading of Recommendation, Assessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 210 publications
0
3
0
Order By: Relevance
“…The overall frequency of intrapulmonary hemorrhage and pneumothorax did not differ significantly across all groups. All pneumothoraces observed in our study were classified as asymptomatic small pneumothorax [30,31], and none of them required further intervention before surgery. No serious complications such as hemoptysis, massive hemothorax or air embolisms were identified in either group.…”
Section: Discussionmentioning
confidence: 76%
“…The overall frequency of intrapulmonary hemorrhage and pneumothorax did not differ significantly across all groups. All pneumothoraces observed in our study were classified as asymptomatic small pneumothorax [30,31], and none of them required further intervention before surgery. No serious complications such as hemoptysis, massive hemothorax or air embolisms were identified in either group.…”
Section: Discussionmentioning
confidence: 76%
“…In this case, the chest CT-scan outperforms the CXR in evaluating pneumothorax size and identifying the causes of secondary pneumothorax. Nevertheless, due to factors such as cost, time constraints, and radiation exposure, it is not recommended as the initial diagnostic examination (Jouneau et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Primary spontaneous pneumothorax (PSP) is a type of spontaneous pneumothorax which occurs in the absence of any trauma or underlying lung disease ( 1 , 2 ). Previous study reported an annual incidence of PSP of 7.4 and 1.2 cases per 100,000 men and women, respectively ( 3 ).…”
Section: Introductionmentioning
confidence: 99%